Magnetotransport measurements on beta ''-(BEDT-TTF)(4)[(H3O)Ga3+(C2O4)(3)](center dot) C6N5NO2 - Bangura, A; Coldea, A; Singleton, J; Ardavan, A; Klehe, A; Akutsu-Sato, A; Akutsu, H; Turner, S; Day, P (2003)
Transport measurements have been carried out on single crystals of the charge transfer salt beta"-(BEDT-TTF)(4)[(H3O) Ga3+ (C2O4)(3)]. C6H5NO2, using magnetic fields of up to 33 T and temperatures down to 0.55 K. The material is found to be superconducting with T. 7.5 K and an in-plane critical field B-c2 greater than or equal to 33 T, and to exhibit Shubnikov-de Haas (SdH) oscillations. The temperature and angle dependence of the Shubnikov-de Haas oscillations and the upper critical field are reported, allowing information about the anisotropy of the upper critical field, effective mass m*, and the Fermi-surface (FS) of the material to be deduced.